Analysis of Nuclear Law and Nuclear Power Plant Development Plans in Indonesia - Gumilang Fuadi; Nanik Prasetyoningsih (Faculty of Law, Universitas Pekalongan, 2023)
This research discusses Nuclear Law Analysis and Nuclear Power Plant Development Plans in Indonesia. The nuclear legal framework is an essential infrastructure in developing nuclear power plants in a country. This research aims to determine the current legal framework for nuclear power in Indonesia and examine the strengthening of nuclear law, which is needed as infrastructure for developing nuclear power plants in Indonesia. This research is normative or dogmatic, using conceptual, statutory and comparative approaches. Data collection techniques include conducting literature studies and searching for primary and secondary legal materials in this research. The results of the study show that the nuclear legal framework in Indonesia has been realized through various ratifications of international electricity legal instruments and national regulations through the Nuclear Energy Law (UUK) as the legal basis and various derivative regulations covering almost all aspects of electricity. . laws, including the mandate to build nuclear power plants in Indonesia. However, considering that UUK is over 20 years old and reflects the Fukushima Daichi nuclear accident, Indonesia's nuclear legal framework as nuclear power plant infrastructure needs to be strengthened. This strengthening covers the four pillars of nuclear law, namely safety, security, safeguards and liabilities, which can encourage the construction of the first nuclear power plant in Indonesia for energy independence and realizing net zero emissions with strict safety and security standards to achieve this goal. Protect citizens and the environment.